Cardiovascular involvement in patients with pseudoexfoliation syndrome - NADİR, AYDIN; ULUS, TANER; Nadir, AYDIN; Yaz, Yasemin Aydin; ÖZDEMİR, ATİLLA ÖZCAN; MUTLU, FEZAN; Yazici, Huseyin Ugur; ÇAVUŞOĞLU, YÜKSEL; YILDIRIM, NİLGÜN (My University, 2013)
AimPseudoexfoliation (PEX) syndrome, diagnosed by ocular examination, is a common disorder of the extracellular matrix. Previous studies have demonstrated accumulation of PEX material in the walls of blood vessels and myocardium. We aimed to investigate whether PEX is associated with cardiovascular involvement using carotid ultrasound measurements and myocardial tissue Doppler imaging (TDI).MethodsThirty-six PEX patients and 34 age-matched and sex-matched healthy controls who had no PEX material were included. Fasting blood samples were taken and the following data were obtained from all cases: myocardial TDI measurements, the mean carotid intima-media thickness (IMT), total carotid plaque area and number.ResultsThere were no significant differences between the groups regarding clinical and biochemical data. The peak systolic TDI velocities at the septal (septal S) and lateral annuli (lateral S), and the isovolumic contraction velocity at the lateral annulus [lateral isovolumic contraction velocity (IVC)] were significantly lower in patients with PEX, than in controls (P=0.001, <0.001 and 0.016, respectively) whereas IMT, total carotid plaque area and number were significantly higher (P=0.002, 0.035 and 0.033, respectively). In a logistic regression analysis including age, septal S, lateral S, lateral IVC, IMT, total carotid plaque area and number, septal S, lateral S and IMT were significantly associated with PEX, (P=0.035, 0.011 and 0.035, respectively).ConclusionPeak systolic TDI velocities were significantly lower and IMT was significantly increased in patients with PEX. However, PEX was weakly associated with carotid plaque measurements.